Respuesta :

Answer:

Step-by-step explanation:

3

The required formula with b subject is [tex]b = a^{2} - 6[/tex].

Given that ,

a is the subject of the formula,

[tex]a = \sqrt{ b + 6}[/tex]

We have to make b is the subject for the formula,

[tex]a = \sqrt{ b + 6}[/tex]

Squaring both the sides,

[tex]a^{2} = b + 6[/tex]

[tex]b = a^{2} - 6[/tex]

Hence , The required formula with b subject is [tex]b = a^{2} - 6[/tex]

For more information about the Square of roots click the link given below.

https://brainly.in/question/9953556

ACCESS MORE